Electrodes for energy storage devices

Electrostatic deposition of deaggregated binder and conductive particles on a conductive substrate addresses the non-uniformity and safety issues of solvent-based methods, enhancing the performance and efficiency of electrochemical energy storage devices.

JP2025504074AActive Publication Date: 2025-02-06AM BATTERIES INC

Patent Information

Application Number
JP2024545749
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-05
Filing Date
2023-01-31
Publication Date
2025-02-06
Estimated Expiration
2043-01-31

AI Technical Summary

Technical Problem

Conventional solvent-based methods for forming electrodes in electrochemical energy storage devices pose handling, ventilation, and safety issues, and result in non-uniform coating layers that affect the performance of batteries.

Method used

The use of electrostatic deposition techniques to form solvent-free electrode coatings by depositing composite particles containing active material, binder, and optionally conductive particles directly on a conductive current collector, where the binder particles are deaggregated into subparticles to enhance adhesion and uniformity.

Benefits of technology

This method results in highly uniform electrode coatings that improve energy storage device performance by reducing manufacturing costs and energy consumption, while ensuring effective adhesion and uniformity of the composite particle layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504074000001_ABST
    Figure 2025504074000001_ABST
Patent Text Reader

Abstract

Electrochemical energy storage device electrodes formed from electrostatic deposition processes use composite particles that include an attached binder and optionally conductive particles along with active material (AM) particles formed by interaction forces between the individual component particles sufficient to form an effective composite particle capable of overcoming particle separation during electrostatic charging, fluidization, and / or mechanical transport. The secondary binder particles undergo deagglomeration to form subparticles attached to the AM particles with a predetermined morphology. Smaller conductive particles, typically carbon black (CB) or similar carbon, bind to the binder and adhere to the AM particles. The result is a composite particle that is attached to withstand the separation forces imposed on the current collector by electrostatic deposition. Applying multiple composite particles in a uniform pattern and at a defined loading onto the conductive current collector promotes robust energy density, power density, and cycle life for the electrochemical energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to a U.S. provisional patent application entitled "ELECTRODE FOR ENERGY STORAGE DEVICE," filed on January 31, 2022 and assigned Serial No. 63 / 304,907, and a U.S. nonprovisional patent application entitled "ELECTRODE FOR ENERGY STORAGE DEVICE," filed on April 5, 2022 and assigned Serial No. 17 / 713,722. The entire contents of the foregoing provisional and nonprovisional applications are incorporated herein by reference.

[0002] 1.Technical Field The present disclosure is directed to electrochemical energy devices and associated methods of manufacturing. The disclosed electrochemical energy devices generally include an electrode, where the electrode comprises a coating layer formed at least in part by depositing dry composite particles on a conductive substrate by an electrostatic deposition process. The composite particles include active material particles and binder particles surrounding the active material particles, where the binder particles are generally formed from deagglomeration of binder agglomerates and are attached to the surfaces of the active material particles through particle-to-particle adhesion forces. [Background technology]

[0003] 2.Background technology Electrochemical energy storage devices have electrodes that contain coating layers in communication with conductive current collector layers, typically copper or aluminum sheets. The coating layers may include cathode and anode active materials, and are often combined with conductive and binder materials to form a structure that readily discharges and accepts charge (is charged) in response to an applied electrical load or charging potential. The formation of the electrochemically active materials, binders, and conductive particles can vary depending on the applicable battery chemistry and production method.

[0004] Conventional approaches to battery manufacturing use a solvent-based approach to form electrodes, which typically involve a binder solution or suspension to flow or apply electrochemically active materials and conductive particles onto a conductive current collector foil. Conventional methods generally involve solvents that pose handling, ventilation, and safety issues, and require drying times for the liquid solvent to evaporate or to fuse the components in the coated layer. Summary of the Invention [Problem to be solved by the invention]

[0005] In general, to produce batteries having optimal energy density, power density and cycle life, it is desirable to form a coating layer in which the electrochemically active material, conductive particles and binder are uniformly dispersed at a density that promotes electrical communication between the electrochemically active material and the current collector. Improvements are desired in methods of applying the coating layer and in the electrochemically active materials formed thereby. These and other objectives are met by the methods and apparatus of the present disclosure. [Means for solving the problem]

[0006] Electrodes for electrochemical energy storage devices are provided that are formed from an electrostatic deposition process using composite particles that include electrochemically active material (or active material "AM") particles and attached binder particles, and optionally conductive particles, formed by sufficient interaction between individual component particles to form effective composite particles that are capable of overcoming / withstanding forces that separate the particles during electrostatic charging and fluidization in the electrostatic deposition process.

[0007] Commercially available binder or conductive materials are generally available in the form of aggregates formed by the physical interaction of multiple primary particles, often referred to as secondary particles. According to the present disclosure, the binder aggregates undergo deagglomeration to form sub-particles and attach to the AM particles having a predetermined and / or desired morphology. It should be noted that the conductive aggregates also form sub-particles through deagglomeration. The sub-particles include one or more primary particles having a smaller size than the original aggregates. In forming the advantageous energy storage device of the present disclosure, the binder particles and conductive particles are incorporated in the form of sub-particles.

[0008] Typically, according to the present disclosure, carbon black (CB) or similar carbon is bound to a binder and adheres to the AM particles along with the binder. The result is a composite particle that exhibits sufficient adhesion to withstand the separation forces imposed during the electrostatic deposition process. In a typical electrostatic spray deposition (ESD) process, the composite particles disclosed herein are aerated and fluidized by a gas flow, carried by the gas flow, and deposited in a uniform pattern and density on a conductive current collector. Alternative electrostatic deposition approaches may also be used.

[0009] The composite particle layer deposited on the current collector may be further densified according to the present disclosure to form an electrode for a battery. The uniformity of the deposited composite particle layer is critical to the performance of the resulting battery. The uniformity of the deposited composite particle layer involves, among other things, the matching of stoichiometry between the deposited layer and the feedstock powder mixture, as well as the matching of stoichiometry and shape within the deposited layer.

[0010] There is considerable commercial interest in the battery industry in applying electrostatic deposition techniques to form solvent-free electrode coatings for Li-ion batteries. In particular, the solvent-free electrode coating technique is attractive because ESD techniques can significantly reduce the energy consumption in the manufacturing process, which can significantly reduce the manufacturing costs of batteries. In principle, the use of electrostatic deposition techniques allows for simpler and more versatile electrode coatings in the manufacture of energy storage devices, since the composite electrode powder is directly deposited on the metal current collector through the electrostatic spray deposition process.

[0011] In conventional applications, electrostatic deposition techniques are widely used in dry powder coating of conductive parts. In conventional applications of electrostatic deposition coating techniques, the quality of the coating layer, especially the uniformity of the coating layer, is directly related to and dependent on the properties of the particles contained in the coating powder. These properties include particle size, dielectric constant, conductivity, density, and morphology. According to the present disclosure, the properties of the particles associated with the coating powder are selected such that the electrostatic deposition coating formed with the disclosed composite particles advantageously promotes / provides a uniform electrode for battery applications.

[0012] The compositions herein can advantageously meet the need for reliable batteries across a range of end-use applications, particularly including electric vehicles (EVs), which are subject to significant current draws to provide adequate vehicle performance. Unfortunately, as noted above, conventional approaches to battery manufacturing use a solvent-based approach to form electrodes, which typically involve binder solutions or suspensions to flow or apply electrochemically active materials and conductive particles onto a conductive current collector foil. Conventional methods involve solvents that impose handling, ventilation, and safety issues, and require drying times for the liquid solvent to evaporate or to fuse the components within the coated layer. Thus, the compositions herein substantially overcome the above-mentioned shortcomings of solvent-based battery formulations by providing electrodes comprising composite particles on a conductive current collector for dry powder applications using an electrostatic deposition approach.

[0013] As disclosed herein, the desired morphology or structure of the composite particles results from the deagglomeration, mixing and adhesion between the component particles to form active material (AM) particles with attached binder and optionally conductive particles in a form that withstands electrostatic deposition processing. When deposited onto a conductive current collector substrate, the disclosed AM particles form / define the correct loading and microstructure for high performance batteries. It should be noted that "loading" is the unit coating layer mass over a specific area, typically in mg / cm2. 2 It is a unit.

[0014] As disclosed herein, advantageous electrodes are formed on a conductive current collector by electrostatic deposition of composite particles, thereby forming a highly effective electrode / electrochemical energy storage device. The disclosed electrodes / electrochemical energy storage devices generally include a plurality of composite particles adapted for electrostatic deposition on a conductive current collector substrate, each composite particle including one or more active material particles, binder particles surrounding the active material particles, and conductive particles attached to the binder particles. The disclosed binder particles are generally formed through deagglomeration of binder agglomerates to form subparticles. The binder particles are attached to the surfaces of the active material particles through interaction forces sufficient to withstand the powder mixing process. The interaction is also sufficient to overcome the separation forces caused by the electrostatic deposition process, which is ideal for maintaining the structure of the composite particles when formed on the conductive current collector substrate by the electrostatic deposition process. Effect of the Invention

[0015] The disclosed electrochemical energy storage devices and methods for their production are highly advantageous in providing effective energy storage capabilities without the need for solvent-based manufacturing methods.

[0016] Additional features, functionality, and advantages of the disclosed electrochemical energy storage devices and related manufacturing methods will become apparent from the detailed description that follows, particularly when read in conjunction with the accompanying drawings.

[0017] The foregoing and other features will become apparent from the following description of specific embodiments set forth herein, as illustrated in the accompanying drawings in which like reference characters refer to the same parts throughout the various views. The drawings are not necessarily to scale, emphasis instead being placed upon illustrating the principles of the invention. [Brief description of the drawings]

[0018] [Figure 1] 1 is a diagram of a composite particle, where Composite particle 101C represents a composite particle as disclosed herein. [Diagram 2] FIG. 2 shows a context / example system for deploying the composite particle of FIG. 1 (composite particle 101C) in an electrochemical energy storage device. [Figure 3A] FIG. 2 illustrates an example composition of the composite particle of FIG. 1. [Figure 3B] FIG. 2 illustrates an example composition of the composite particle of FIG. 1. [Figure 4] FIG. 4 illustrates the progression through the formation of the composite particle of FIGS. 1-3B. [Figure 5A] 1 is an SEM image of the mixed powder for Sample 1. [Figure 5B] 1 is an SEM image of the mixed powder for sample 3. [Figure 5C] 1 is an SEM image of the mixed powder for sample 4. [Figure 6A] 13 is a SEM image of a larger area of ​​the mixed powder for Sample 1. [Figure 6B] 13 is a SEM image of a larger area of ​​the mixed powder for Sample 3. [Figure 6C] 13 is a SEM image of a larger area of ​​the mixed powder for Sample 4. [Figure 7A] 1 is an EDS image (nickel mapping) of the mixed powder for Sample 1. [Figure 7B] 1 is an EDS image (nickel mapping) of the mixed powder for sample 3. [Figure 7C] 1 is an EDS image (nickel mapping) of the mixed powder for sample 4. [Figure 8A] 1 is an EDS image (fluorine mapping) of the mixed powder for sample 1. [Figure 8B] 1 is an EDS image (fluorine mapping) of the mixed powder for sample 3. [Figure 8C] 1 is an EDS image (fluorine mapping) of the mixed powder for sample 4. [Figure 9] 1 is a plot showing bond strength for electrodes prepared by electrostatic spray deposition using powders at various mixing times and speeds in accordance with the present disclosure. [Figure 10]1 is a SEM image of composite particles (NCM 622 / PVDF / carbon) deposited on an Al substrate according to the present disclosure. [Figure 11] 13 is an EDS mapping image of composite particles (NCM 622 / PVDF / carbon) deposited on an Al substrate showing the distribution of Ni active particles according to the present disclosure. [Figure 12] 13 is an EDS mapping image of composite particles (NCM 622 / PVDF / carbon) deposited on an Al substrate showing the distribution of carbon particles relative to Ni active particles according to the present disclosure. [Figure 13] 13 is an EDS mapping image of composite particles (NCM 622 / PVDF / carbon) deposited on an Al substrate showing the distribution of PVDF binder particles relative to Ni active particles according to the present disclosure. [Figure 14] 1 is a plot of resistance versus mixing time for an electrode made by depositing composite particles onto a substrate using ESD. [Figure 15] 1 is a plot of bond strength versus mixing time for an electrode made by depositing composite particles onto a substrate using ESD. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Depicted below are example methods and machines for forming and deploying composite particles in electrochemical energy storage devices, such as rechargeable batteries. Other particle deposition approaches may be used to couple the composite particles to current collectors or other energy storage devices that store and release electrical energy (electrons) to provide electrical current in a controlled and efficient manner.

[0020] As described herein, the term "particle" generally refers to a granular quantity of particulate matter adapted to mix and interact with other particles. The morphology of the particles may be spherical or any other form. Examples referring to individual particles are intended to be illustrative of the presence of particles in a granular quantity of particles, including powder and granular forms, or interactions that affect some or all of them. It should be further noted that in battery terminology, "active charge material" is often referred to as "electrochemically active material" or "electrode active material". Electrostatically deposited materials thus deposited as disclosed herein may also be referred to as "coating layers" depending on the context.

[0021] Agglomeration of particles often occurs in bulk granular materials, including electrochemical active materials, binder materials, and conductive materials, which are involved in the manufacture of electrochemical energy storage devices according to the present disclosure. All of these materials take the form of particles, which may be in the form of aggregates, meaning that multiple primary particles interact through relatively weak forces that are broken down through agitation and mixing. In common nomenclature, aggregates refer to secondary particles, which upon agitation are broken down into primary particles or sub-particles. Although the processes and methods discussed herein generally serve to form individual primary particles from sub-particles of broken, scrambled, or stirred aggregates, particles as defined herein include primary particles, secondary particles, sub-particles of aggregates, and any interactions or bonds between particles of a particular type. In other words, clusters of primary particles, often referred to as secondary particles or aggregates, are generally expected to separate into smaller particles upon agitation, although certain aggregates remain intact and may still define a particle of the respective active material, binder, or conductive material, meaning that particle and / or its sub-particles in any form. Thus, a particle may break down into multiple subparticles, each of which is still a particle, nonetheless. In addition, the force applied during the mixing process may be sufficient to break up agglomerated particles.

[0022] FIG. 1 is a diagram of the composite particles disclosed herein. The configurations herein apply a solvent-free (dry) electrostatic spray deposition (ESD) coating technique for battery composite electrode fabrication with high uniformity. The present disclosure further enables a composite powder mixing process to produce a suitable composite powder mixture for ESD electrode coating. Alternative applications include any electrochemical storage device, such as fuel cells.

[0023] The battery has a cathode and an anode. In a typical Li-ion battery, the cathode and anode are based on a composite electrode powder mixture. The composite electrode powder mixture generally contains active electrode material particles (AM), binder material particles (binder) and conductive material particles (CB). The active electrode material may be a cathode material, such as lithium metal oxide-based cathode materials: NCM (lithium nickel cobalt manganese oxide), LMO (lithium manganese oxide), NCA (lithium nickel cobalt aluminum oxide), LCO (lithium cobalt oxide), and lithium polyanion-type cathode materials: LFP (lithium iron phosphate), LiMn x Fe 1-x PO4, Li2FeSiO4, as well as carbonaceous anode materials, graphite, Si, Si-based composites, SiO x , lithium alloyable materials, or lithium transition metal oxide anode materials. In a typical sodium-ion battery, the cathode material is a sodium transition metal oxide, e.g., Na 2 / 3 Fe 1 / 2 Mn 1 / 2O2, sodium polyanion materials such as Na2MnSiO4, Prussian Blue Analogues cathode materials such as Na2MnFe(CN)6. And anode materials include carbonaceous anodes, materials capable of forming an alloy with sodium, sodium transition metal oxides or Prussian Blue analogues anode materials. Transition metal oxide-based cathode materials such as NCM have been used for about 10 -6 ~10 -7 It is a semiconductor with an electronic conductivity of 1.0 S / cm.

[0024] Typical binder materials are polymeric materials, such as PVDF (polyvinylidene fluoride), PTFE (polytetrafluoroethylene), PEO (polyethylene oxide) or PMMA (poly(methyl methacrylate)), SBR (polystyrene butadiene rubber binder), CMC (carboxymethyl cellulose binder) or PAA (polyacrylic acid), which are electrical insulators. The binder material may also be a polymer electrolyte, such as PEO / lithium triflate polymer electrolyte. Furthermore, the binder may be a solid-state electrolyte complex consisting of an inorganic solid electrolyte and a polymeric binder, a polymer electrolyte binder or an organic binder, such as Li3InCl6 / PMMA complex, LLZO / polymer electrolyte complex.

[0025] The conductive material may include carbon black (CB), carbon nanotubes, or graphene, which are electrically conductive. In addition, some functional additives may be included in the composite electrode. These additives may be, for example, silica, alumina, zirconium oxide, or any combination thereof.

[0026] The true density of the cathode material is generally 4-5 g / cc for NCM and 3.6 g / cc for LFP. The true density of the binder is typically in the range of 1-2 g / cc. Typical particle sizes for the active material are in the range of 1-40 μm. The binder material typically has a primary particle size of 100-1000 nm and an aggregate size of 5-30 μm. The conductive material typically has a primary particle size of 40-80 nm. The conductive current collectors are typically Al and Cu foils with or without a prime layer to enhance adhesion between the coated layer and the conductive substrate. Such an adhesion layer may be applied to the conductive substrate prior to deposition.

[0027] Referring to FIG. 1, an electrode formed by electrostatic spray deposition (ESD) for an electrochemical energy storage device according to the present disclosure includes a plurality of composite particles adapted for electrostatic deposition onto a conductive current collector substrate. Each composite particle of the plurality of composite particles (or at least a majority of the composite particles) includes an active material particle and a binder particle surrounding the active material particle. According to the present disclosure, the binder particles are formed either by breaking down binder aggregates into subparticles or by directly introducing prefabricated subparticles. In either case, the binder particles adhere to the surface of the active material particles through binding forces that are greater than the interaction forces that are broken during such agitation based on the forces introduced into the system through agitation of the binder aggregates. A conductive additive may be added to form the composite.

[0028] In FIG. 1, the particles in the region 100 depict an example cathode material for an electrochemical energy storage device. In the composite electrode powder mixture, the weight ratio of active material is usually more than 80%, and the weight ratio of binder and conductive material is less than 20%, to enable sufficient gravimetric energy density and acceptable / useful power density for the battery. The composite electrode powder mixture is prepared by a mixing process to enable uniform dispersion of the component particles. FIG. 1 illustrates several dispersion patterns of particles 101A, 101B, and 101C of the component particles in the composite electrode powder mixture that is thoroughly mixed through dry mixing. The component particles include AM, binder, and conductive particles, however, as will become clear in the following discussion, in some configurations, conductive materials are not necessary and / or included in the composite electrode.

[0029] In general, the AM particles 111 are the largest particles, the binder particles 112 are smaller but varying (shown as hatched shading), and the conductive particles 113 (shown as solid lines) are in the smallest particle size range. However, in certain embodiments, the sizes and size relationships can vary widely. In particle 101A, the binder 112 either has a large sub-particle size or is in the form of aggregates. The active material 111 particles retain their original morphology during dry mixing. In the static powder form, all particles are well dispersed, but there is no strong interaction between the AM 111, the binder 112, and the CB (conductive) particles 113.

[0030] Particle 101B shows that the binder 112 aggregates are advantageously broken in the mixing process and the sub-particle size is smaller than that of the active material 111. The active material particles keep their original morphology during dry mixing. With 101A, in static powder form, particles 111, 112 and 113 may be well dispersed, but there are no strong interaction forces between the AM, binder and CB particles.

[0031] Particle 101C depicts a composite particle in which the binder agglomerates are broken in the mixing process and the size of the subparticles 112 is smaller than the active material 111. The active material particles retain their original morphology during mixing. In static powder form, the binder particles and conductive particles are individually coated on the surface of the active material particles by surface fusion, van der Waals attraction, or various potential physical interactions and chemical bonds. Composite particle 101C is adapted for electrostatic deposition onto a current collector substrate based on the binder subparticles stirred to break up the agglomerates, and the interaction forces are sufficient to withstand separation forces caused by material handling, electrostatic deposition onto a substrate, and post-deposition handling to maintain the morphology of the composite particle 101C.

[0032] It should be noted that the significant effect on the binder / active particle ratio related to the deagglomeration of the binder particles through the mixing process disclosed herein can be calculated based on theory. Thus, as shown in Table 1 below, for an average particle size of 0.1 μm for the binder particles, the binder / active particle ratio increases to 53,819, compared to 431 for the binder particles that are 0.5 μm and 54 for the binder particles that are 54 μm. Thus, the dispersion of the binder particles relative to the active particles (assumed to be 10 μm) increases by several orders of magnitude according to the present disclosure.

[0033] [Table 1]

[0034] A variety of AM particle and composite particle formulations can be achieved. A distinction should be noted between the component particles of AM, binder and conductive material, which are generally obtained as uniform bulk granular materials, and the composite particles formed for electrostatic deposition, which are formed by particle-particle interaction forces. In an exemplary arrangement, the active material is formed from a transition metal oxide for electrochemical energy storage devices as a cathode material. Exemplary cathode materials typically include NCM (lithium nickel cobalt manganese oxide), LFP (lithium iron phosphate), LCO (lithium cobalt oxide), or other suitable formulation chemistry, based on the form that can receive and release lithium ions. Cathode materials can often be formulated prior to deposition by proprietary methods as opposed to bulk products. The active material formed by the disclosed methods can also be an anode material for electrochemical energy storage devices. Exemplary deployments of the active material are for rechargeable batteries, with chemistries defined by rechargeable lithium batteries, Li-ion batteries, rechargeable Li-S batteries, solid-state batteries, rechargeable sodium batteries, and sodium-ion batteries. The binder particles are generally formed from one or more of polymeric materials, polymer electrolytes, and solid state electrolyte complexes, several specific compounds being named above.

[0035] FIG. 2 shows a context / example system for deploying the composite particles of FIG. 1 into a battery. The ESD manufacturing method 200 includes an electrostatic deposition applicator 215 and a hopper 216. A feedstock 214 includes a bulk amount of the composite particles 101C described above. The composite particles 101C are generated by a mixer 130 having an agitator 132 or a similar approach for mixing, combining, and attaching the composite particles 101C. The source of bulk particles includes active material 150-1, binder particles 150-2, and optionally conductive particles 150-3 (generally 150). The source 150 is provided to the mixer 130 in a predetermined amount, generally at least 80% by weight of active material. The source 150 is obtained from any suitable commercial or industrial source, typically as a homogenous bulk stock, and has a granular, particulate, or powder structure. Particles and powders should be considered interchangeable in the discussion herein.

[0036] After mixing, the binder particles are typically between 200-1000 nm and the conductive particles are between 100-500 nm. Once mixed, the mixer 130 contains the composite electrode mixture 160 for the feedstock 214. The AM particles are typically considerably larger than the attached binder and conductive particles, generally ranging from 1-40 μm, discussed further below.

[0037] As shown in FIG. 2, the composite particles of FIG. 1C are depicted as constituent particles for a cathode material in an electrostatic deposition apparatus 250. The active material can be either a cathode material or an anode material, formed from cathode material or anode material particles, respectively. The composite particles from the feedstock 214 are aerated and fluidized by a pressurized gas flow, usually dry air. The fluidized composite particles are carried by the gas flow through an electrostatic applicator 215 where they are charged, move through an electric field, and are finally deposited on a grounded conductive current collector 254 to form a composite particle layer 252. The composite particles, fluidized and carried by the gas flow, are charged by corona or triboelectric charging in the electrostatic applicator 215.

[0038] The output product of the electrostatic deposition manufacturing method 200 is a coated sheet 253, which includes a composite particle layer 252 and a substrate 254. The electrostatic deposition applicator 215 can be any suitable electrostatic deposition device. Although a spray process is often involved, other electrostatic deposition approaches may be employed. The coated sheet 253 is densified to form an electrode for an electrochemical energy storage device. The coated sheet 253 can also be preheated prior to densification. The densification process can be with or without heating. The above process can create a cathode or an anode. The densification process can be repeated, for example, multiple times. For electrostatic charging of the composite particles, the electrostatic applicator can use any suitable electrostatic approach. Electrostatic application can include corona charging, tribocharging, direct electrode induction charging, or other suitable charging processes.

[0039] An electrochemical energy storage device, such as a Li-ion battery, has a cathode, an anode, a separator, and an electrolyte. The cathode typically includes an active material, such as NCM, a binder material, such as PVDF, and a conductive material, such as carbon black. The anode typically includes an active material, such as graphite, a binder material, such as PVDF or SBR / CMC binder, and / or a conductive material, such as carbon black. The separator is typically a porous polymer film that separates the cathode and the anode and allows ionic transport between the cathode and the anode. The electrolyte is typically a lithium salt solution, such as a solution of LiPF6 salt and EC / DMC / EMC solvent, and provides ionic conduction between the cathode and the anode.

[0040] In the loading or discharging mode, the anode undergoes oxidation and the cathode undergoes reduction. In the charging mode, the anode undergoes reduction and the cathode undergoes oxidation. The energy stored in the electrochemical storage device depends not only on the electrochemical energy stored by the active material, but also on the content of the active material in the electrodes. Furthermore, the uniformity of the current distribution in the electrochemical energy storage device significantly affects the cycle life of the device. The uniformity of the current distribution is directly related to the uniformity of the electrodes. The structural characteristics of the electrodes, such as porosity and thickness, affect the power capacity of the electrochemical energy storage device.

[0041] Characteristics that are affected by forming and layering the charged material include the uniformity of the electrode, the active material loading in the electrode, the porosity of the electrode, the electrical conductivity, the processability of the electrode, the power density and cycle life of the resulting battery, which are directly related to the energy density.

[0042] In electrostatic processing 200, the charge on a particle is calculated according to the following formula:

[0043]

number

[0044] Typical particle size ranges for cathode materials are in the range of 1-40 μm. Typical primary particle sizes for PVDF binders are 200-300 nm. Typical primary particle sizes for conductive carbons are 40-50 nm. From the above equations, the maximum charge on a particle is directly related to the square of the particle radius, so the charge on the individual powder components during electrostatic deposition can vary by several orders of magnitude.

[0045] Cathode materials typically have a much higher dielectric constant than the polymeric binder materials: for example, PVDF has a dielectric constant of about 8-10 at 21° C., while lithium nickel oxide based cathode materials have a dielectric constant of the order of 1000.

[0046] The relaxation time t for charge dissipation from an ideal charged body is τ=ε0ε r / σ (In the formula, ε r = dielectric constant of the powder, and σ = electronic conductivity of the powder) is given by:

[0047] The electronic conductivity of NCM cathode materials is generally around 10 -6 ~10 -7 S / cm, and PVDF is 10 -14 S / cm, which results in a difference of several orders of magnitude in the relaxation time for charge dissipation.

[0048] Based on the above analysis, the active material particles, binder particles and conductive material particles have different electrostatic deposition behaviors in the electrostatic deposition process due to the significant differences in chargeability and charge dissipation time resulting from differences in conductivity, dielectric constant, particle size and density.

[0049] In addition, differences in particle size, particle density, morphology, surface roughness, and therefore surface energy will cause them to behave differently as they relate to aerodynamic effects during powder fluidization and mechanical transport to the surface to be coated.

[0050] In the absence of strong interaction forces between particles in the mixture, significant segregation may occur during coating due to differences in electrostatic deposition and fluidization behavior related to powder properties, leading to detrimental effects on coating uniformity in terms of composition, microstructure, and dimensions. Conventional approaches result in a deposited layer 252 with varying stoichiometry due to different deposition patterns from the individual component particles, for example, from the feedstock 214.

[0051] In electrostatic deposition process 200 using conventional techniques, active material particles, binder particles, and conductive material particles (formed as 101A and 101B) are individually charged as the powder particles pass through a spatial charging zone in a corona, tribo, or direct plate electrode electrostatic charging system. Due to differences in chargeability and charge dissipation time, the individually charged particles are deposited on the current collector, causing non-uniformity in the deposited layer.

[0052] During the formation of the composite particles 101C according to the present disclosure, the small binder particles and conductive material particles are added / attached onto the surface of the active material particles to form the composite particles. During the aeration or mechanical transport and deposition of the composite particles consisting of the active material particles with the binder and conductive material particles added onto the surface, the composite particles become charged and accumulate, resulting in a uniform deposition on the current collector substrate 254. Furthermore, due to the high resistivity of the binder particles 112, the charge dissipation time of the composite particles is longer than that of the pure active material particles, which allows electrostatic forces to have an effect during handling after coating until the binder curing operation can be performed. Therefore, the composition of the composite particles 101C in the feedstock 214 electrode powder mixture is particularly beneficial for electrostatic deposition to achieve a high degree of uniformity.

[0053] 3A and 3B show an example composition of the composite particle of FIG. 1. Referring to FIGS. 1 through 3A-3B, FIG. 3A shows a composite particle 101C having AM particles 111 and attached binder particles 112. FIG. 3B shows that the composite particle 101C further comprises conductive particles 113. Depending on the arrangement of the mixer 130, the composite particle 101C can be formed from simultaneously mixing the conductive particles 113, the active material particles 111, and the binder particles 112. In an alternative configuration, the composite particle 101C further comprises combining the conductive particles 113 for attachment to the surface of the binder particles 112, and subsequently attaching the combined binder and conductive particles to the surface of the AM particles 111 to form the composite particle 101C.

[0054] Any mixing / particle coating equipment, such as an impact mixer or shear mixer, can be used to achieve the composite electrode powder mixture formed with composite particles 101C. The binder agglomerates are broken down to form sub-particles and the conductive material agglomerates are broken down into smaller particles. These sub-particles attach / attach to the surface of the active material particles by surface melting, van der Waals attraction, or a variety of potential physical interactions or chemical bonds to create a sufficiently large interaction force between the individual particles to form an effective composite particle that can overcome particle separation during electrostatic charging, fluidization, mechanical transport, and / or deposition processes.

[0055] FIG. 4 shows the progression through the formation of the composite particle of FIGS. 1-3B (e.g., composite particle 101C). An important property of mixing and stirring is to break down binder agglomerates 112′ into sub-particles 112, if such agglomerates are present in the raw material source. The stirring also reduces the conductive particles 113′ into smaller sub-particles 113 that are more suitable for attachment to the AM particles 111. The mixing / stirring disclosed herein is sufficient to break the interaction forces 401 between the agglomerates, yet cause the binder 112 to adhere to the AM particles 111 with binding forces 402 that are greater than the separation forces encountered through the electrostatic deposition system 200, thereby maintaining the morphology of the composite particle 101C and providing uniform deposition of layer 252.

[0056] The sizes shown in FIG. 4 are for illustrative and example purposes only. In actual production, the size of the binder subparticles 112 is expected to range between 0.1% to 70% of the average size of the active material particles 111. When the average particle size of the active material is greater than 5 μm, it is beneficial if the average subparticle size of the binder is less than 10% of the active material. When the average particle size of the active material is less than 5 μm, the preferred average subparticle size of the binder is less than 70% of the active material.

[0057] Granular feedstock 150 can be expected to exhibit particle size variations and is generally expected and normal to be in a range of sizes. As long as the overall range exhibits typical distributions and averages, stray particles outside the ranges shown herein are unlikely to have a negative effect. Similar distribution ranges can be tolerated for the agglomerates and sub-particles discussed above, and not all agglomerates / secondary particles can always be expected to be broken down with strict uniformity.

[0058] The subparticle size of the conductive material is 1-100% of the average subparticle size of the binder. The subparticle size of the conductive material is preferably less than 30% of the average subparticle size of the binder. From the constituent or component particles, not all of the binder 112 and conductive particles 113 may adhere to the active material particles 111. In the electrode powder mixture, more than 50% by weight of the binder subparticles should be applied to the surface of the active material particles. It is preferred that more than 80% by weight of the binder subparticles be applied to the surface of the active material particles. More than 50% by weight of the conductive subparticles are applied to the surface of the binder subparticles. And more than 50% of the binder / conductive composite particles are applied to the surface of the active material particles. It is preferred that more than 80% by weight of the binder and conductive material are applied to the surface of the active material particles.

[0059] When the composite electrode mix does not contain a conductive material, the binder subparticles are applied directly to the surfaces of the active material particles.

[0060] The active material powder, binder powder and / or conductive material powder can be simultaneously loaded into the mixer and mixed. It is preferred to premix the binder and conductive material and then mix with the active material powder, so as to better break down the binder and conductive aggregates and increase the interaction between the binder subparticles and the conductive material.

[0061] Some additional particle stock sizings are as follows: The sub-particle size of the conductive material is 1-100% of the average sub-particle size of the binder. It is preferred that the sub-particle size of the conductive material is less than 30% of the average sub-particle size of the binder.

[0062] In an alternative arrangement, the method of attaching / adhering the binder / conductive particles to the active material particles is not limited to the dry powder mixing described herein. For example, in one exemplary embodiment, the binder / conductive material particles can be coated onto the active material particles through mixing a suspension or solution of the binder / conductive material with the active material powder. In another exemplary embodiment, the binder particles can be coated onto / to the surface of the active material particles through a spray drying process.

[0063] In a particular use case, the mixer 130 uses a high shear mixer to mix the NCM / binder / CB powder mixture with standard binder sub-particle sizes for electrostatic deposition. The high shear mixer provides a unique rotating mixing pan with built-in eccentric mixing tools. The mixing speed can be set in the range of 1-30 m / s to disperse and mix particles with different sizes. In this example, an active material (NCM) with a size around 10 μm, a PVDF binder with a primary size of 200-300 nm, and a conductive carbon with a primary size of 40-50 nm were used. The AM / binder / CB particles with a weight ratio of 96:2:2 were mixed for 30 minutes using the high shear mixer. SEM imaging of the mixed particles shows a coating of CB and binder on the surface of the AM. EXAMPLES

[0064] 1. Material Preparation and Electrode Preparation by Electrostatic Spray Deposition Batches of 700 g of powder mixture containing heat treated NMC, PVDF and carbon black in a weight ratio of 90:7:3 were loaded into a high shear mixer. Mixing studies were carried out at different mixing speeds and times (sample 1: 12 m / s, 10 min; sample 3: 20 m / s, 20 min; sample 4: 25 m / s, 20 min).

[0065] The mixed NMC powder was loaded into a hopper in an electrostatic spray deposition system. The dry powder was fluidized by conveying gas under vibration. The fluidized powder was charged by a corona electrostatic spray gun and deposited on a grounded Al foil with a thickness of 15 μm. The coating side of the Al foil was pre-coated with a PVDF interface layer with a thickness of less than 1 μm, which was applied by electrostatic spray deposition technique. The deposited sample was heated at 250° C. on a hot plate for about 1 hour to melt the binder. Finally, the annealed sample was pressed to the desired thickness using a roller press to achieve 35% porosity. The electrode sample is ready for SEM / EDS, adhesion and electrochemical testing.

[0066] 2. SEM / EDS examination of samples 1, 3 and 4 The mixed powder samples were analyzed by SEM / EDS to evaluate the deagglomeration of PVDF / carbon particles and the coating of PVDF / carbon on NMC particles. As shown in Figure 5A, a few aggregates of PVDF / carbon can be seen attached to the NMC surface, but most of the NMC surface is exposed. The structure of the NMC surface is clearly visible. This indicates that under 12 m / s, 10 min mixing, the surface of NMC is barely covered by PVDF / carbon particles.

[0067] As the mixing intensity increases to 20 m / s, 20 min (sample 3, FIG. 5B) and 25 m / s, 20 min (sample 4, FIG. 5C), the surface of the NMC particles is completely covered by PVDF / carbon.

[0068] 6A-6C show SEM images of larger areas of the mixed powders for Sample 1 (FIG. 6A), Sample 3 (FIG. 6B) and Sample 4 (FIG. 6C).

[0069] The corresponding EDS results are shown in Figure 7A (Sample 1, nickel mapping), Figure 7B (Sample 3, nickel mapping) and Figure 7C (Sample 4, nickel mapping), and Figure 8A (Sample 1, fluorine mapping), Figure 8B (Sample 3, fluorine mapping) and Figure 8C (Sample 4, fluorine mapping). ImageJ was used to process the elemental mapping images to remove the effect of signal intensity on image quality. The maximum intensity of each element is reported in the images.

[0070] The nickel distribution can be fully mapped to the corresponding SEM images as shown in Figures 7A-7C. The overall shape of the individual NMC particles is captured by the nickel mapping. Fluorine mapping, an indicator of PVDF content (Figures 8A-8C), shows striking differences between the three blended materials.

[0071] The fluorine mapping image of 12 m / s, 10 min mixing (Figure 8A) does not reveal the generally spherical shape of the NMC particles, indicating that most of the PVDF particles are still randomly located in the mixed powder, rather than attached to the NMC particles. The tightly packed black spots (indicated by arrows) near the bottom left corner of the image also indicate that some PVDF particle agglomerates were not broken down under low intensity mixing.

[0072] With more intense mixing, the fluorine begins to concentrate, revealing the spherical shape of the NMC particles, as shown at 20 m / s, 20 min (Sample 3, FIG. 8B) and 25 m / s, 20 min (Sample 4, FIG. 8C). The tightly packed black spots (indicated by arrows) near the center left of the fluorine mapping for the 20 m / s, 20 min mix (Sample 3, FIG. 8B) indicate large agglomerates of PVDF particles. From the corresponding SEM image in FIG. 6B, it can be seen that the NMC particles are behind this large agglomerate of PVDF particles, but the PVDF agglomerates completely block the nickel x-ray spectrum that is collected by the detector. Therefore, they are shown as spaces (indicated by arrows) in the corresponding nickel mapping image. The large PVDF agglomerates are not visible in the powder mixed at 25 m / s, 20 min (Sample 4). A relatively uniform distribution of PVDF particles is achieved, as can be seen from the corresponding fluorine mapping image in FIG. 8C.

[0073] 3. Adhesion test The bond strength of the electrodes was evaluated using a pull-off test. The electrode samples were cut into disks with a diameter of 14.3 mm. The disks of the electrodes were attached to a flat head tip with a diameter of 12.7 mm using double-sided tape. The disks were attached to the base with double-sided tape with a compressive force of 15 N, and then pulled, recording the maximum tensile force that caused the disk to collapse. Figure 9 is a plot showing the bond strength for electrodes prepared by electrostatic spray deposition with powders at various mixing times and speeds, i.e., samples 1, 3, and 4. The plot in Figure 9 shows that the samples prepared with longer mixing times demonstrated better adhesion.

[0074] 4. EDS Mapping of Electrodes In a further exemplary embodiment of the present disclosure, the binder particles were subjected to deagglomeration to form the composite particles described herein above, and the composite particles were deposited on an aluminum foil substrate by electrostatic spray deposition, followed by thermal calendering. This exemplary embodiment has a binder particle density of 20 mg / cm 2The composite particles in the electrode are made of NCM 622 / PVDF / carbon with a loading of 0.01g / cc and a density of 3.7g / cc. The PVDF and carbon interact with the active particles to provide strong adhesion and electrical conductivity.

[0075] As shown in the SEM images in Figure 10, the composite particles exhibit strong adhesion to the Al substrate.

[0076] As shown in the EDS mapping image in FIG. 11, the Ni active particles are uniformly distributed and adhered to the Al substrate.

[0077] As shown in the EDS mapping image in FIG. 12, the carbon particles are uniformly distributed and adhered to the Ni active particles.

[0078] As shown in the EDS mapping image in FIG. 13, the PVDF binder particles are uniformly distributed and adhered to the Ni active particles (based on the imaging showing the fluorine distribution).

[0079] 5. Results of the Mixing Study A series of tests were conducted to determine the relationship between the mixing conditions related to the formation of composite particles and the performance of these composite particles when deposited on a substrate by ESD. A batch of 700 g of powder mixture containing heat treated NMC, PVDF and carbon black in a weight ratio of 96:2:2 was loaded into a high shear mixer. Mixing studies were conducted using various mixing speeds and mixing times. The resistance across the thickness of the fabricated electrodes was measured by sandwiching the electrode disc between two measurement plates.

[0080] As shown in the plot of FIG. 14, the resistance associated with the composite particles deposited on the substrate (which is a measure of the uniformity of carbon distribution for the composite particles deposited on the substrate) indicates that a favorable operating window is established for mixing times between about 8 and 35 minutes. Mixing times less than 8 minutes yielded unacceptably high resistance levels (approximately 33 ohms). Significantly longer mixing times (approximately 50 minutes) did not improve the results, but rather demonstrated approximately equivalent resistance performance when compared to mixing of shorter duration, e.g., approximately 30 minutes.

[0081] Turning to Figure 15, the bond strength (which is a measure of the uniformity and effectiveness of the binder distribution for the composite particles deposited on the substrate) associated with the composite particles deposited on the substrate shows that for mixing times between about 8 and 35 minutes, a favorable operating window is established - the same operating window as identified by the resistance measurements described above with reference to Figure 14. Mixing times less than 8 minutes resulted in unacceptably low bond strengths. Significantly longer mixing times (approximately 50 minutes) did not improve the results, but rather demonstrated approximately equivalent average bond strengths and a much broader range of performance when compared to mixing of shorter duration, e.g., approximately 30 minutes.

[0082] Based on the test results shown in FIGS. 14 and 15, mixing times between about 8 minutes and about 35 minutes are effective in forming composite particles exhibiting good distribution and retention of adhesion / attachment of the binder particles and conductive particles to the active particles according to the present disclosure.

[0083] The disclosed electrochemical energy storage devices can be incorporated into various assemblies / subassemblies, such as rechargeable lithium batteries, Li-ion batteries, rechargeable lithium-sulfur batteries, solid state batteries, rechargeable sodium batteries, and / or sodium-ion batteries.

[0084] While the systems and methods defined herein have been particularly shown and described with reference to embodiments thereof, those skilled in the art will understand that various changes in form and details may be made therein without departing from the scope of the invention as encompassed by the appended claims.

Claims

1. A conductive collector substrate, One or more electrostatically deposited coating layers deposited on and adhered to a conductive current collector substrate. An electrode comprising: the one or more electrostatically deposited coating layers comprise a plurality of dry mixed composite particles, each dry composite particle of the plurality of dry mixed composite particles comprising (i) one or more active material particles and (ii) deagglomerated binder particles surrounding each of the one or more active material particles; the deagglomerated binder particles adhere to a surface of one of the one or more active material particles through interactions sufficient to survive the mixing involved in forming a dry composite particle and to overcome separation forces resulting from deposition of one or more electrostatically deposited coating layers on a conductive current collector substrate; This maintains the structure of the composite particles when applied onto a conductive current collector substrate, the electrode.

2. 10. The electrode of claim 1, wherein one or more active material particles function as a cathode material.

3. 3. The electrode of claim 2, wherein the one or more active material particles are selected from (i) lithium transition metal oxides, lithium transition metal sulfides, lithium polyanion cathode materials including lithium transition metal phosphates, lithium transition metal silicates, or combinations thereof, or (ii) sodium transition metal oxides, sodium polyanion cathode materials, Prussian blue analog cathode materials, or combinations thereof.

4. 10. The electrode of claim 1, wherein one or more active material particles function as an anode material.

5. The one or more active material particles are selected from the group consisting of: (i) a carbonaceous anode material, graphite, Si, a Si-based composite, SiO x 5. The electrode of claim 4, wherein the anode material is selected from: (i) a material capable of alloying with lithium, or a lithium transition metal oxide anode material, or a combination thereof; or (ii) an ion intercalation anode material comprising a material capable of alloying with sodium, or a Prussian blue analog anode, and a sodium metal transition metal oxide anode.

6. 10. The electrode of claim 1, wherein the structure is incorporated into an assembly selected from the group consisting of a rechargeable lithium battery, a Li-ion battery, a rechargeable lithium-sulfur battery, a solid-state battery, a rechargeable sodium battery, and a sodium-ion battery.

7. 10. The electrode of claim 1, wherein the deagglomerated binder particles are formed from one or more of a polymeric material, a polymer electrolyte, and a solid state electrolyte complex.

8. 8. The electrode of claim 7, wherein the polymeric material is selected from polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, poly(methyl methacrylate), polystyrene butadiene rubber binder, carboxymethyl cellulose binder, polyacrylic acid, or combinations thereof.

9. 10. The electrode of claim 1, wherein the dry mixed composite particles further comprise conductive particles adhered to a surface of at least one of the one or more active material particles and the deagglomerated binder particles.

10. 10. The electrode of claim 9, wherein the conductive particles are selected from the group consisting of carbon black, carbon nanotubes, carbon fibers, graphene, graphite, or combinations thereof.

11. 10. The electrode of claim 1, wherein the conductive current collector substrate is selected from Al or Cu foil.

12. 12. The electrode of claim 11, further comprising a prime layer to enhance adhesion between the one or more electrostatically deposited coating layers and the conductive current collector substrate.

13. 10. The electrode of claim 1, wherein the size of the deagglomerated binder particles is between 0.1% and 70% of the average size of the one or more active material particles.

14. 10. The electrode of claim 1, wherein the average size of the one or more active material particles is greater than 5 μm and the average size of the deagglomerated binder particles is less than 10% of the average size of the one or more active material particles.

15. 10. The electrode of claim 1, wherein the average size of the one or more active material particles is less than 5 μm and the average size of the deagglomerated binder particles is less than 70% of the average size of the one or more active material particles.

16. 10. The electrode of claim 1, wherein the dry mixed composite particles further comprise conductive particles, and greater than 50% of the deagglomerated binder particles and conductive particles are attached to an active material particle of the one or more active material particles.

17. 1. A method of forming an electrode, comprising the steps of: combining the one or more active material particles and the deagglomerated binder particles to form a plurality of dry mixed composite particles, the deagglomerated binder particles surrounding each of the one or more active material particles; Depositing the plurality of dry mixed composite particles onto a surface of a conductive substrate by an electrostatic deposition process. A method comprising:

18. Deagglomerating the binder material to form deagglomerated binder particles.

20. The method of claim 17, further comprising:

19. combining conductive particles with one or more active material particles and deagglomerated binder particles, the conductive particles adhering to surfaces of the deagglomerated binder particles; and followed by adhering the combined binder and conductive particles to the surface of one or more active material particles to form composite particles.

20. The method of claim 17, further comprising:

20. 18. The method of claim 17, wherein the electrostatic deposition process is selected from the group consisting of corona-charged electrostatic deposition, tribo-charged electrostatic deposition, and direct electrode induction-charged electrostatic deposition.

21. 18. The method of claim 17, comprising forming deagglomerated binder particles from the binder material by combining one or more active material particles and a binder material and agitating the dry mixture to overcome cohesive forces and form deagglomerated binder particles from the binder material, whereby the deagglomerated binder particles adhere to a surface of the one or more active material particles to form composite particles having sufficient interaction forces between the deagglomerated binder particles and the one or more active material particles to maintain adhesion during electrostatic charging, fluidization, and mechanical transport.

22. 22. The method of claim 21, wherein the stirring provides sufficient force to pulverize the dry mixture.

23. Adhering the plurality of dry mixed composite particles to a surface of the conductive substrate includes depositing the plurality of composite particles onto the conductive substrate to form a coating layer having a predetermined active material loading; The method further includes densifying the coating layer and the conductive substrate through a densification treatment selected from the group consisting of: (i) preheating the coating layer and the conductive substrate followed by a densification treatment; (ii) preheating the coating layer and the conductive substrate followed by densification under heat; and (iii) densifying the coating layer and the conductive substrate under heat. The method of claim 21.

24. 24. The method of claim 23, wherein the densification process is repeated.

25. The method of claim 21, wherein the agitation results in deagglomerated binder particles of a size between 200 and 1000 nm.

26. 20. The method of claim 17, wherein the combining step comprises combining the conductive particles with one or more active material particles and the deagglomerated binder particles to form a plurality of dry mixed composite particles, whereby the conductive particles are adhered to the deagglomerated binder particles.

27. deagglomerated binder particles are formed from the binder material by combining one or more active material particles and the binder material and agitating the dry mixture to overcome cohesive forces and form deagglomerated binder particles from the binder material; the structure of the one or more active particles is maintained during the stirring and attachment to the surface of the conductive substrate; deagglomerated binder particles are formed by deagglomerating a binder material; combining the one or more active material particles and the deagglomerated binder particles to form a plurality of dry mixed composite particles includes agitating the one or more active material particles and the deagglomerated binder particles in a solvent-free manner to adhere the deagglomerated binder particles and to maintain the morphology of the one or more active material particles during agitation; The method of claim 17.

28. combining the deagglomerated binder particles with the conductive particles such that the conductive particles adhere to the deagglomerated binder particles; and Adhering the combined deagglomerated binder particles and conductive particles to the surface of one or more active material particles to form a dry mixed composite particle. Further comprising: the dry mixed composite particles having less than 20 weight percent of the combined conductive particles and deagglomerated binder particles; the average size of the binder particles is less than 50% of the average active material particle size; the average size of the conductive particles is less than 30% of the average size of the deagglomerated binder particles; The method of claim 17.

29. 20. The method of claim 17, further comprising forming an electrode from the conductive substrate having the dry mixed composite particles adhered thereto.

30. 20. The method of claim 17, further comprising including in the battery a conductive substrate having the dry mixed composite particles adhered thereto.

Citation Information

Patent Citations

  • Manufacturing method of electrode

    JP2001351616A

  • Method of manufacturing electrode

    JP2014137965A

Cited By

  • Negative electrode active material, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    WO2026191279A1